Pi‐Stacking Enhances Stability, Scalability of Formation, Control over Flexibility, and Circulation Time of Polymeric Filamentous Nanocarriers. Issue 11 (5th August 2021) - Li, Sophia; Bobbala, Sharan; Vincent, Michael P.; Modak, Mallika; Liu, Yugang; Scott, Evan A.
Abstract : Self‐assembling filomicelles (FMs) are of great interest to nanomedicine due to their structural flexibility, extensive systemic circulation time, and amenability to unique "cylinder‐to‐sphere" morphological transitions. However, current fabrication techniques for preparing FMs are highly variable and difficult to scale. Herein, it is demonstrated that tetrablock copolymers composed of poly(ethylene glycol)‐ b ‐poly(propylene sulfide) (PEG‐ b ‐PPS) diblocks linked by a pi‐stacking perylene bisimide (PBI) moiety permit rapid, scalable, and facile assembly of FMs via the flash nanoprecipitation (FNP) method. Coassembling the tetrablocks and PEG‐ b ‐PPS diblocks at different molar ratios resulted in mixed PBI‐containing FMs (mPBI‐FM) with tunable length and flexibility. The flexibility of mPBI‐FM can be optimized to decrease uptake by macrophages in vivo, leading to increased circulation time versus (−)PBI‐FM without PBI tetrablocks after intravenous administration in mice. While PEG‐ b ‐PPS diblocks form FM within a narrow range of hydrophilic weight fractions, incorporation of pi‐stacking PBI groups expanded this range to increase favorability of FM assembly. Furthermore, the aggregation‐dependent fluorescence of PBI shifted during oxidation‐induced "cylinder‐to‐sphere" transitions of mPBI‐FM into micelles, resulting in a distinct emission wavelength for filamentous versus spherical nanostructures. Thus, incorporation of pi‐stacking allows for rapid, scalable assembly of FMs with tunable flexibility and stability for theranostic and nanomedicine applications. Abstract : Coassembly of pi‐stacking perylene bisimide (PBI)‐containing tetrablock copolymers with diblock copolymers enhances the stability, scalable formation, and control over flexibility of polymeric filamentous nanocarriers. When compared with PBI‐free filaments, mixed PBI filaments with an optimal flexibility demonstrate reduced uptake by mouse macrophages in vitro and in vivo, increased circulation times, and an altered biodistribution after intravenous administration in mice.